PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Hasanah, Yulia; Syofni, Syofni; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was a classroom action research that aimed to improve learning process and increase student mathematics achievement with applied the learning model of Discovery Learning. The subject of this research was students of class VIIIB SMPN 1 Kampar Utara in odd semester in academic year 2018/2019, around 16 students, consisted of six boys and 10 girls. The research consist of two cycles, each cycle had four stages, which are planning, implementation, observation, and reflection. The instruments of data collection in this research were observation sheets and students mathematic tests. The observation sheets were analyzed by narrative descriptive analysis technique, while the students’ mathematic tests result was analyzed by descriptive statistical analysis technique. The qualitative descriptive showed an improvement of learning process before the action on the first cycle to second cycle. Most of the students were very enthusiastic and seemed to be confidence and active in learning process. The results of this study indicated the number of students who reached Minimum Mastery Criteria increase from basic score (37,5 %) to UH-I (56,25 %) up to UH-II (68,75%) and on competency skill increase from UH I (31,25%) to UH II (56,25%) thus it could be concluded that the implementation of Discovery Learning model can improve the learning process and increase mathematics achievement of the students at class VIIIB SMPN 1 Kampar Utara in odd semester in academic year 2018/2019 for the main material of Relasi dan Fungsi.Key Words: Students’ Mathematic Achievement, Discovery Learning, Class Action Research